Population dynamics of mesenchymal stromal cells during culture expansion - Schellenberg, Anne; Stiehl, Thomas; Horn, Patrick; Ho, Anthony Dick (Cytotherapy, 2012)
Background aims: Mesenchymal stromal cells (MSC) are heterogeneous and only a subset possesses multipotent differentiation potential. It has been proven that long-term culture has functional implications for MSC. However, little is known how the composition of subpopulation changes during culture expansion. METHODS: We addressed the heterogeneity of MSC using limiting-dilution assays at subsequent passages. In addition, we used a cellular automaton model to simulate population dynamics under the assumption of mixed numbers of remaining cell divisions until replicative senescence. The composition of cells with adipogenic or osteogenic differentiation potential during expansion was also determined at subsequent passages. Results: Not every cell was capable of colony formation upon passaging. Notably, the number of fibroblastoid colony-forming units (CFU-f) decreased continuously, with a rapid decay within early passages. Therefore the CFU-f frequency might be used as an indicator of the population doublings remaining before entering the senescent state. Predictions of the cellular automaton model suited the experimental data best if most cells were already close to their replicative limit by the time of culture initiation. Analysis of differentiated clones revealed that subsets with very high levels of adipogenic or osteogenic differentiation capacity were only observed at early passages. Conclusions: These data support the notion of heterogeneity in MSC, and also with regard to replicative senescence. The composition of subpopulations changes during culture expansion and clonogenic subsets, especially those with the highest differentiation capacity, decrease already at early passages.Arrayed high-throughput screens (HTS) cover a broad range of applications using RNAi or small molecules as perturbations and specialized software packages for statistical analysis have become available. However, exploratory data analysis and integration of screening results has remained challenging due to the size of the data sets and the lack of user-friendly tools for interpretation and visualization of screening results. Here we present HTSvis, a web application to interactively visualize raw data, perform quality control and assess screening results from single to multi-channel measurements such as image-based screens. Per well aggregated raw and analyzed data of various assay types and scales can be loaded in a generic tabular format.
Gesehen am 17.04.2018